Indonesian Language Learning Strategies in Increasing the Learning Interest of Grade VIII Students at SMP IT As Syakur, Bengkulu City - Novi Prita Bona; Edi Ansyah; Meddyan Heriadi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to identify the strategies used by Indonesian language teachers in the learning process to enhance the interest in learning Indonesian among eighth-grade students at SMP IT As Syakur, Bengkulu City, and how the interest of eighth-grade students at SMP IT As Syakur, Bengkulu City, in learning Indonesian. The type of this research is descriptive qualitative. The location of this research is at SMP IT As Syakur in Bengkulu City. Using data collection techniques such as observation, interviews, and documentation. Based on the research results, the strategy for teaching Indonesian to increase students' interest in learning at SMP IT As Syakur in Bengkulu City is by using discussion methods, providing motivation, learning evaluations, and quizzes. The interest of eighth-grade students at SMP IT As Syakur in Bengkulu City towards learning Indonesian is quite high, as evidenced by four indicators of interest: feelings of happiness, student interest, student attention, and student involvement in learning activities.